#### Answer

Please see the graph.
(-1,-3)

#### Work Step by Step

$y=-x-4$
$-3 = -1*-1-4$
$-3 = 1-4$
$-3 = -3$
$4x-y=-1$
$4*-1--3=-1$
$-4 +3 = -1$
$-1 = -1$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

Please see the graph.
(-1,-3)

$y=-x-4$
$-3 = -1*-1-4$
$-3 = 1-4$
$-3 = -3$
$4x-y=-1$
$4*-1--3=-1$
$-4 +3 = -1$
$-1 = -1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.